Insulin secretion hot spots in pancreatic β cells as secreting adhesions - Fye, Margret A.; Kaverina, Irina (Frontiers in Cell and Developmental Biology, 2023)
Pancreatic β cell secretion of insulin is crucial to the maintenance of glucose homeostasis and prevention of diseases related to glucose regulation, including diabetes. Pancreatic β cells accomplish efficient insulin secretion by clustering secretion events at the cell membrane facing the vasculature. Regions at the cell periphery characterized by clustered secretion are currently termed insulin secretion hot spots. Several proteins, many associated with the microtubule and actin cytoskeletons, are known to localize to and serve specific functions at hot spots. Among these proteins are the scaffolding protein ELKS, the membrane-associated proteins LL5β and liprins, the focal adhesion-associated protein KANK1, and other factors typically associated with the presynaptic active zone in neurons. These hot spot proteins have been shown to contribute to insulin secretion, but many questions remain regarding their organization and dynamics at hot spots. Current studies suggest microtubule- and F-actin are involved in regulation of hot spot proteins and their function in secretion. The hot spot protein association with the cytoskeleton networks also suggests a potential role for mechanical regulation of these proteins and hot spots in general. This perspective summarizes the existing knowledge of known hot spot proteins, their cytoskeletal-mediated regulation, and discuss questions remaining regarding mechanical regulation of pancreatic beta cell hot spots.